P59An epigenetic signature regulates gene expression in cardiac hypertrophy. (15th July 2014) - Kunderfranco, P; Cattaneo, P; Greco, CM; Carullo, P; Stirparo, GG; Rusconi, F; Hasenfuss, G; Chen, J; Condorelli, G; Papait, R
Abstract: The epigenetic signature for transcription regulation is poorly understood in cardiac hypertrophy. Here, we investigate the genome-wide distribution of several histone modifications and the correlated transcriptome in adult mouse cardiomyocytes subjected to a pro-hypertrophy stimulus in vivo. We demonstrate that the epigenetic profile dynamic of cardiac genes changes in response to the stimulus, and that distinct epigenetic signatures at promoters regulate the gene re-programming occurring with cardiac hypertrophy. Moreover, we identify 9, 207 enhancers that impact transcription in normal and hypertrophic cardiomyocytes and whose activity is governed by unique epigenetic signatures. In fact, combinations of H3K27ac, H3K9ac, and H3K4me3 marks define new subclasses of highly active and dynamic enhancers in cardiac myocytes. We also analyzed the transcriptional network within which these genetic elements act to orchestrate hypertrophy gene expression, finding a role for myocyte enhancer factor (MEF)2C and MEF2A in regulating enhancers. The association of cardiac hypertrophy with a specific epigenetic profile provides a new basis for understanding the molecular mechanisms underlying hear failure, and opens up the possibility of developing new therapies based on the control of the epigenetic profile of cardiomyocytes.